Education and Technologies in the University Context (Docentes 2.0 Journal, 2023)
It is unquestionable that thanks to the use of Information and Communication Technology (ICT), educational systems managed to get ahead during the pandemic; however, the impact of the virtual modality adopted was negative, as demonstrated by indicators of failure and school dropout. In this context, the objective set out in this research work has been to characterize the practices in the use of ICT by teachers of the Centro Universitario del Norte of the University of Guadalajara within the framework of the guidelines and policies to implement online courses. The work was an ethnographic method and paradigm, qualitative approach, and ethnographic design with an explanatory scope and cross-section. Structured interviews, recordings, and records were used as data collection techniques. As for analysis techniques, categorization, and saturation, the population comprised CUNorte teaching staff, and the sample was chosen using the causal method. The results showed a gap between the institutional proposal on the use of technologies and what happened in space-time. The main findings to improve the teaching-learning processes for the benefit of the students are the construction of a techno-pedagogical design as a proposal on the use of ICT and a training program that identifies, prioritizes, and meets the needs of teachers.
Keywords: Education; technologies; teaching